Three essays on regulatory economics - Onemli, Muharrem Burak (Kansas State University, 2010)
Mandatory network unbundling is one of the foremost topics in regulatory economics today. The concept has crucial importance in the deregulation of many previously regulated industries including telecommunications, gas, electricity and railroads. Moreover, the topic has emerged as one of the more prominent issues associated with the implementation of the 1996 Telecommunication Act in the United States. Upon initial examination, establishing the correct costing standards and/or determining the correct input prices would seem important for sending the correct price signals to the entrants for their efficient make-or-buy decisions. Sappington (AER, 2005) uses a standard Hotelling location model to show that input prices are irrelevant for an entrant’s make or buy decision. In this first essay, we show that this result is closely related to the degree of product differentiation when firms are engaged in price competition. Specifically, it is shown that input prices are irrelevant when firms produce homogeneous products, but are relevant for make-or-buy decisions when the entrant and incumbent produce differentiated products. These results suggest that, in general, it is important for regulators to set correct prices in order to not distort the entrants’ efficient make-or-buy decisions. The second essay investigates optimal access charges when the downstream markets are imperfectly competitive. Optimal access charges have been examined in the literature mainly under the condition where only the incumbent has market power. However, network industries tend to exhibit an oligopolistic market structure. Therefore, the optimal access charge under imperfect competition is an important consideration when regulators determine access charges. This essay investigates some general principles for setting optimal access charges when downstream markets are imperfectly competitive. One of the primary objectives of this essay is to show the importance of the break-even constraint when first-best access charges are not feasible. Specifically, we show that when the first-best access charges are not feasible, the imposition of the break-even constraint on only the upstream profit of the incumbent is superior to the case where break-even constraint applies to overall incumbent profit, where the latter is the most commonly used constraint in the access pricing literature. Bypass and its implications for optimal access charges and welfare are also explored. The third essay is empirical in nature and investigates two primary issues, both relating to unbundled network element (UNE) prices. First, as Crandall, Ingraham, and Singer (2004) suggested, we will empirically test the stepping stone hypothesis using a state-level data set that spans multiple years. To do this, we will explore the effect of UNE prices on facilities-based entry. Second, in light of those findings, we will investigate whether the form of regulation (e.g. price cap and rate of return regulation) endogenously affects the regulator’s behavior with respect to competitive entry. Lehman and Weisman (2000) found evidence that regulators in price cap jurisdictions tend to set more liberal terms of entry in comparison with regulators in rate-of-return jurisdictions. This paper investigates whether their result is robust to various changes in modeling, including specification and econometric techniques.
Keywords: Regulatory economics; Make-or-Buy decision; Optimal access charges; UNE Prices; Economics, General (0501); Economics, Theory (0511)